q-Gamow States as continuous linear functionals on analytical test functions - Plastino, Ángel Luis (2016)
We define here q-Gamow states corresponding to Tsallis' q-statistics. We compute for them their norm, mean energy value and the q-analogue of the Breit-Wigner distribution (a q-Breit-Wigner).